Clinical implementation of islet transplantation: A current assessment. Issue 6 (18th June 2015) - Bottino, Rita; Trucco, Massimo
Abstract Beta‐cell replacement is the only physiologically relevant alternative to insulin injections in patients with type 1 diabetes (T1D). Pancreas and islet transplantation from deceased organ donors can provide a new beta‐cell pool to produce insulin, help blood glucose management, and delay secondary diabetes complications. For children and adolescents with T1D, whole pancreas transplantation is not a viable option because of surgical complications, whereas islet transplantation, even if it is procedurally simpler, must still overcome the burden of immunosuppression to become a routine therapy for children in the future.